Improved systolic ventricular function with normal myocardial mechanics in compensated cardiac hypertrophy - Okoshi, Katashi [UNESP]; Ribeiro, Henrique Barbosa [UNESP]; Okoshi, Marina Politi [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Gonçalves, Giancarlo [UNESP]; Barros, Reginaldo [UNESP]; Cicogna, Antonio Carlos [UNESP] (International Heart Journal (Japanese Heart Journal), 2004)
There is still controversy about the relation between changes in myocardial contractile function and global left ventricular (LV) performance during stable concentric hypertrophy. To clarify this, we analyzed LV function in vivo and myocardial mechanics in vitro in rats with pressure overload-induced cardiac hypertrophy. Male Wistar rats (70 g) underwent ascending aortic stenosis for 8 weeks (group AAS, n = 9). LV performance was assessed by transthoracic echocardiography under anesthesia. Myocardial function was studied in isolated papillary muscle preparations during isometric contraction. The data were compared with age- and sex-matched sham-operated rats (group C, n = 9). LV weight-to-body weight ratio (C: 2.13 ± 0.14 mg/g; AAS: 3.24 ± 0.44 mg/g), LV relative wall thickness (C: 0.18 ± 0.02; AAS: 0.33 ± 0.09), and LV fractional shortening (C: 54 ± 5%; AAS: 70 ± 8%) were increased in group AAS (P < 0.05). Echocardiographic analysis also indicated a significant association (r = 0.74; P < 0.001) between the percent fractional shortening index and LV relative wall thickness. The performance of AAS isolated muscle revealed that active tension (C: 6.6 ± 1.7 g/mm2; AAS: 6.5 ± 1.5 g/mm2) and maximum rate of tension development (C: 69 ± 21 g/mm2/s; AAS: 69 ± 18 g/mm2/s) were not significantly different from group C (P > 0.05). In conclusion, compensated pressureoverload myocardial hypertrophy is associated with preserved myocardial function and increased ventricular performance. The improved LV function might be due to the ventricular remodeling characterized by an increased relative wall thickness. Copyright © 2004 by the Japanese Heart Journal.
Keywords: Aortic stenosis; Cardiac function; Echocardiography; Left ventricular hypertrophy; Papillary muscle